Inhomogeneously distributed ferroptosis with a high peak-to-valley ratio may improve the antitumor immune response - Chi, Mau-Shin; Tien, Der-Chi; Chi, Kwan-Hwa (Frontiers in Oncology, 2023)
Combined radiotherapy (RT) and mild hyperthermia have been used clinically for decades to increase local control. Both modalities tend to achieve a homogeneous dose distribution within treatment targets to induce immunogenic cell death. However, marked, and long-lasting abscopal effects have not usually been observed. We proposed a hypothesis to emphasize the importance of the peak-to-valley ratio of the dose distribution inside the tumor to induce immunogenic ferrroptosis in peak area while avoid nonimmunogenic ferroptosis in valley area. Although inhomogeneous distributed energy absorption has been noted in many anticancer medical fields, the idea of sedulously created dose inhomogeneity related to antitumor immunity has not been discussed. To scale up the peak-to-valley ratio, we proposed possible implications by the combination of nanoparticles (NP) with conventional RT or hyperthermia, or the use of a high modulation depth of extremely low frequency hyperthermia or high resolution spatially fractionated radiotherapy (SFRT) to enhance the antitumor immune reactions.